Pengembangan kompetensi kultural dengan menumbuhkan sikap toleransi di Sekolah Menengah Atas - Hanan Early Nofrel Hanan; Isnarmi Moeis; Junaidi Indrawadi; Rita Anggraini (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
This study is motivated by the cultural diversity in Indonesia, which requires an attitude of tolerance through context-appropriate multicultural education that encompasses all learners, particularly in schools with pupils from diverse backgrounds, including those with special educational needs. The aim of this study is to examine how cultural competence can be developed to foster an attitude of tolerance at Yari International School. This study employs a qualitative approach with a descriptive-analytical design. Data were collected through interviews with Pancasila education teachers and school management, direct observation, and existing documents. Data analysis utilised an interactive model comprising several stages reduction, presentation, and drawing of conclusions, and was validated through triangulation of sources and methods. The research findings indicate that the enhancement of cultural competence is achieved by conducting context-appropriate learning, dividing students into culturally diverse groups, holding discussions and addressing issues of diversity, as well as organising extracurricular activities aimed at strengthening character and expressing art and culture.This practice helps to raise awareness of cultural identity, foster empathy towards others, improve intercultural communication skills, and promote non-discriminatory attitudes in everyday interactions. However, there are some challenges, such as initial prejudices and differences in communication styles among students. Nevertheless, with a good communication approach and sufficient support from teachers, these obstacles can be effectively overcome.